Concurrent versus sequential adjuvant chemo-endocrine therapy in hormone-receptor positive early stage breast cancer patients: a systematic review and meta-analysis. (June 2017) - Poggio, F.; Ceppi, M.; Lambertini, M.; Bruzzi, P.; Ugolini, D.; Bighin, C.; Levaggi, A.; Giraudi, S.; D'Alonzo, A.; Vaglica, M.; Blondeaux, E.; Sertoli, M.R.; et al.
Abstract: Background: Although in clinical practice adjuvant chemotherapy (CT) and endocrine therapy (ET) are administered sequentially in patients with hormone-receptor positive breast cancer, the optimal timing, i.e. concurrent or sequential administration, of these treatments has been scarcely investigated. To better clarify this issue we conducted a systematic review and meta-analysis of randomized studies comparing these two modalities of administrations in terms of disease-free survival (DFS) and overall survival (OS). Methods: Relevant studies were identified by searching PubMed, Web of Knowledge and the proceedings of the major conferences with no date restriction up to March 2016. The summary risk estimates (pooled hazard ratio [HR] and 95% confidence intervals [CI]) for DFS and OS were calculated using random effect models (DerSimonian and Laird method). Results: A total of three randomized studies were eligible including 2021 breast cancer patients. Overall, 755 DFS events were observed, 365 in the sequential arm and 390 in the concomitant arm, with a pooled HR of 0.95 (95% CI = 0.76 to 1.18, P = 0.643). No association between timing of treatment and OS was observed (HR = 0.95; 95% CI = 0.80 to 1.12, P = 0.529). Conclusion: Our pooled analysis showed no association between the timing of administration of adjuvant CT and ET and DFS and OS in breast cancer patients candidates for both adjuvant treatments. Because of the small number of published trials, the lack of data on the timing with modern adjuvant treatments, i.e. taxane-containing CT and aromatase inhibitors, this topic remain still controversial and requires further studies to be clarified.